The Role Of Destination Image, City Branding, E-WOM And Travel Consstraint In Singapore Decision To Visit Tourist Attractions In Batam City - Suali, Suali; Heryenzus, Heryenzus (Jurnal Ekonomi, 2024)
This study aims to analyze the role of destination image, city branding, electronic word of mouth (E-WOM), and travel constraints on the decision of Singaporeans to visit tourist attractions in Batam City. This study uses a quantitative method with a survey approach. The number of samples used in this study was 100 Singaporeans.  Data was obtained through the distribution of questionnaires to Singaporeans who have visited or plan to visit Batam City. The data analysis technique used was multiple regression analysis to determine the influence of each variable on the decision to visit. The results of the study show that the image of the destination has a significant influence on the decision to visit, where the positive perception of natural beauty, facilities, and community friendliness is the main attraction. City branding also plays an important role in increasing the awareness and interest of Singaporeans in Batam, especially through the promotion of slogans, city icons, and international events. In addition, E-WOM through online reviews and social media has proven to be effective in building trust and influencing travelers' preferences. Meanwhile, travel constraints, such as travel costs and time, have a negative but relatively small influence given Batam's close distance from Singapore.This study concludes that the combination of a strong destination image, consistent city branding promotion, and optimal use of E-WOM can improve Singaporeans' decision to visit Batam.